Pseudoaneurysm rupture after Acute Necrosis Pancreatitis debuting as Upper Gastrointestinal Bleeding due to Fistulization of the Duodenum - López de la cruz, Julia Lopez (2023)
We present the case of a 64-year-old man who, after a first episode of acute pancreatitis, was readmitted 20 days later due to severe epigastric pain and later an episode of upper gastrointestinal bleeding in the form of hematemesis and melena with hemodynamic instability. An urgent gastroscopy was performed at that time, revealing a probable gastrointestinal fistula in the duodenal bulb with an adherent clot without active bleeding at that time, so an urgent CT angiography was performed that revealed a necrotic peripancreatic collection with the presence of active bleeding inside from the pancreatoduodenal artery. Urgent arteriography identified an image compatible with arterial pseudoaneurysm dependent on the pancreaticoduodenal artery branch, which was successfully embolized. Unfortunately, the patient died a few hours later as a result of septic shock secondary to an infected pancreatic collection.